What motivates physicians to share free health information on online health platforms?. Issue 2 (March 2020) - Zhang, Xiaofei; Guo, Feng; Xu, Tianxue; Li, Yongli
Abstract: Online platforms enable physicians to share health and medical information with the public; however, little research has been conducted to explore why physicians share free health education information. Drawing on motivation theory, this study develops a theoretical model to explore the influences of material and professional motivation on free information sharing and the contingent roles of professional expertise and online expertise. The model is tested using a six-month panel data set of 61, 326 physicians' sharing experiences. The results indicate that in addition to material motivation, professional motivation also plays a primary role in inducing physicians to share free information. However, when a physician's professional and online expertise is at a high level, the effect of material motivation is weakened and professional motivation plays a more important role. This study contributes to the literature on knowledge sharing, online health behavior, and motivation theory, and provides implications for practice.